A Rare Cause of Right-Sided Air Bubble on Chest Radiograph: Intrathoracic Gastric Volvulus Related to Morgagni Hernia - Sahin, Abdurrahman; Artas, Hakan; Yalniz, Mehmet (S. Karger AG, 2017)
Morgagni hernia is a rare disorder in adulthood, and most of the cases are asymptomatic. Symptomatic cases are extremely rare and present with life-Threatening complications. Early diagnosis and surgery are lifesaving. We hereby present an adult case of symptomatic Morgagni hernia. Diaphragmatic herniation of the stomach and mesenteroaxial rotation led to intrathoracic gastric volvulus in this case. A right-sided air bubble on a chest radiogram was the only finding leading to the suspicion of diaphragmatic hernia. Computed tomography in the diagnosis of diaphragmatic hernias is of great importance. © 2017 The Author(s).
Keywords: Diaphragmatic hernia; Intrathoracic gastric volvulus; Morgagni; Upside-down intrathoracic stomach